The Effectiveness of Health Education of Breasfeeding Preparation on Primigravida Mothers Motivation to Provide Exclusivation - Ika Agustina (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2018)
Exclusive breastfeeding is the pure one without additional fluids, either formula, water orange juice or other supplementary foods before reaching the age of six month. Giving breasfeeding is very benefical for baby, mother, family, and country. The purpose of this study was to analyze the effect of health education on breasfeeding preparation of mother s motivation to provide exclusive breasfeeding. The type of the study used pre-experimental design. The populastion used in this study was 15 primi- gravida mothers. The sample was 15 respondents taken by Consecutive sampling technique. The instrumen used questionnaire sheet. The statistical test used Paired Sample t Test. The results showed that the motivation of mother primigravida after being given health education become strong motivation equal to 40%. The resulth of analysis using Paired Sample t Test Test showed the value of p value=0,000, so p value=0,000 <0,05 or significant, it meant that there was an effect of health education of breasfeeding preparation to motivate primigravida mothers to give exclusive breasfeeding. Based on the results of the study is expected to primigravida motherss to improve health education in the preparation of breasfeeding and to health workers further increase the primigravida mother s mitigation to provide exclusive ation to achieve exclusive ation success.